DESIGN OF BUSINESS PERFORMANCE EVALUATION IN MUAMALAT NU COOPERATIVE WITH A BALACED SCORECARD APPROACH - Tigin Lugiani; Mutqi Sopiawadi (STIESA Press, 2023)
The Balanced Scorecard is a management, measurement and control system that quickly, precisely, comprehensively can provide managers with an understanding of business performance. The balanced scorecard applied to the Muamalat Nahdlatul Ulama cooperative is an economic institution for the small people, founded by Nahdhiyin Kasomalang residents who have the desire to work towards productive endeavors in increasing the economic activities of small entrepreneurs based on cooperative and sharia principles. The Muamalat Nahdlatul Ulama Cooperative is a means of managing funds from the ummah by the ummah and for the ummah (Economic Democracy). There are 4 perspectives in BSC, namely: 1. customer perspective, 2. Internal business process perspective, 3. financial perspective, 4. learning and growth perspective. Adjustedto financial circumstances.